ANALISIS SPIRITUAL VALUE, STRES KERJA PEKERJA MUSLIM SEKTOR FORMAL KOTA MEDAN - Tri Niswati Utami; Nuraini Nuraini (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2016)
ABSTRACT Formal workers (white collar) are professional jobs that require certain training and skills. Formal sector workers government agencies and non-government such as: corporate, institutional and industrial demand time and home work, good performance, demands adequate skills and productivity work well too. This condition causes the pressure by the workers and lead to job stress. Research method: using a two stage approach: qualitative and quantitative. Quantitative design uses one group pretest posttest study. Bivariate data analysis paired t test and PLS (Partial Least Square). Results and Discussion: before training, the majority of study subjects spiritual value less category as many as 16 people (94.1%), after increasing the value of spiritual spiritual training, the majority of both categories as many as 10 people (58.8%). Statistical test results Smart PLS found 1 indicator invalid ie, patient indicator (0420). Valid indicators, namely: thanks to God (.842), sincere (0.926) and happy (0.605). Conclution: spiritual indicator value: thanks to God, cincere and happy. Spiritual training improve the spiritual value. Keyword: spiritual value, work stress, syukur pada Allah, cincere, happy